2015
DOI: 10.1212/wnl.0000000000001409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of VZV in temporal arteries of patients with giant cell arteritis

Abstract: Most GCA-positive TAs contained VZV in skip areas that correlated with adjacent GCA pathology, supporting the hypothesis that VZV triggers GCA immunopathology. Antiviral treatment may confer additional benefit to patients with GCA treated with corticosteroids, although the optimal antiviral regimen remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
148
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(161 citation statements)
references
References 29 publications
8
148
1
2
Order By: Relevance
“…They found that 74 % of TAs in GCA-positive cases contained VZV antigen, mostly in skip (multiple noncontiguous) areas, whereas only 8 % of normal TAs did so. Typical inflammatory histopathology was detected in 89 % of GCA-positive TAs but not in any of the 18 adjacent tissue sections from normal TAs [32]. A very recent follow-up study by these authors found that VZV antigen was present in 64 % of GCA-negative TAs compared with 22 % of normal TAs [33].…”
Section: Giant Cell Arteritismentioning
confidence: 84%
See 2 more Smart Citations
“…They found that 74 % of TAs in GCA-positive cases contained VZV antigen, mostly in skip (multiple noncontiguous) areas, whereas only 8 % of normal TAs did so. Typical inflammatory histopathology was detected in 89 % of GCA-positive TAs but not in any of the 18 adjacent tissue sections from normal TAs [32]. A very recent follow-up study by these authors found that VZV antigen was present in 64 % of GCA-negative TAs compared with 22 % of normal TAs [33].…”
Section: Giant Cell Arteritismentioning
confidence: 84%
“…GCA is characterized pathologically by inflammation in and damage to the vessel wall of the temporal arteries (TAs) [31,32]. The condition may be strongly suspected on clinical grounds, with symptoms including headache, scalp tenderness, weight loss, malaise, and raised erythrocyte sedimentation rate, and the diagnosis is confirmed by a TA biopsy showing the typical inflammatory histopathological features.…”
Section: Giant Cell Arteritismentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of temporal artery biopsies from healthy individuals aged >50 years and from patients with arteritis revealed VZV antigen in the temporal arteries of 61 out of 82 (74%) of patients with arteritis compared with 1 out of13 (8%) in normal temporal arteries 88 . This discovery, if confirmed, suggests that antiviral treatment might confer additional benefit to corticosteroids in patients with giant cell arteritis.…”
Section: Neurological Complications Of Zostermentioning
confidence: 96%
“…VZV and giant cell arteritis-One of the most exciting recent developments is the detection of VZV antigen, VZV DNA and virus particles in the temporal arteries of patients with giant cell arteritis (inflammatory vasculopathy, most often involving the temporal arteries) 88 . Analysis of temporal artery biopsies from healthy individuals aged >50 years and from patients with arteritis revealed VZV antigen in the temporal arteries of 61 out of 82 (74%) of patients with arteritis compared with 1 out of13 (8%) in normal temporal arteries 88 .…”
Section: Neurological Complications Of Zostermentioning
confidence: 99%